Impact of acute kidney injury in patients with acute decompensated heart failure: Cardiorenal syndrome - Tandel, Sagar; Mishra, Ashish; Jain, Sharad; Sharma, Vishal; Kanabar, Kewal; Vyas, Pooja; Patel, Krutika; Desai, Nisarg; Kedia, Aman (The Indonesian Heart Association, 2023)
Cardiorenal syndrome (CRS) is a complex interdependent relationship between the heart and kidneys, prevalent in hospitalized patients with acute decompensated heart failure (ADHF). The main aim of this study is to evaluation of cardiac and renal function, treatment factors, and outcomes in view of mortality and persistent renal dysfunction in acute decompensated heart failure (cardio renal syndrome type 1) patients. We studied 100 patients hospitalised with ADHF and acute kidney injury (AKI). Patients were evaluated clinically, biochemically, ultrasonographically, and echocardiographically to assess demographics, etiologic and risk factors, cardiac and renal function, and outcomes in view of mortality and persistent renal dysfunction. The study monitored the patients until discharge and follow up with three months to one year. Record information about functional improvement, worsening symptoms, and mortality. The majority of the patients were males (72%), with dyspnea being the most common symptom (92%) followed by decreased urinary output (82%). The mean age of the patients was 62.60 years. Low level of Mean arterial pressure (MAP) 18.97 (95% CI 4.59 to 78.37, P 0.0001), estimated glomerular filtration rate (eGFR) 0.92(95% CI 0.87 to 0.99; P 0.02), maximum creatinine 3.08 (95% CI 1.67 to 5.67, P 0.0001), maximum level of urea 1.02(95% CI, P 0.001), lower Left ventricular ejection fraction (LVEF) 1.05 (95% CI 0.15 to 0.84, P 0.04) were independently predictors of in-hospital mortality. CRS-1 is associated with increased risk of mortality (25%), residual renal dysfunction (16%) at one year follow up. Persistent renal dysfunction, renal replacement therapy possibly improves for the treating persistent renal dysfunction, and recurrent HHF (more than 2 admissions) post hospitalisation index within twelve months were predictors of mortality (25%) at one-year.This article has a related Erratum.